Why commuting matters: Horizontal and vertical tax externalities in the Belgian federation - Willem Sas (European Regional Science Association (ERSA), 2013)
Looking at the Belgian federation, where 10% of the working population commutes across the borders of three small regions, a case can be made for studying commuting flows in a federal constellation. In this paper, commuting is introduced to a federal setting where an ad valorem residence based tax on labour income is fully decentralised. This has lower-level (state) governments set inefficiently low taxes not to attract more workers, but to boost labour supply of own residents and hamper labour supplied by non-residents. When the labour tax base is co-occupied by the federal and state governments alternatively, either public under- or overprovision may occur. Our model identifies clear conditions for states to overprovide, i.e. for the overall fiscal externality to be negative. Moreover, such a negative externality may arise even when the vertical as well as horizontal externalities are positive in isolation, and one would rather expect underprovision. Lastly, when states differ in terms of preferences and technology, an inflow of commuters will make it more likely for states to set taxes inefficiently low. Second choice for topic: Special Session - S_J
Keywords: 330; Fiscal federalism; tax competition; horizontal and vertical externalities; commuting